High-protein energy-restricted diets induce greater improvement in glucose homeostasis but not in adipokines comparing to standard-protein diets in early-onset diabetic adults with overweight or obesity. Issue 5 (May 2020) - Marco-Benedí, Victoria; Pérez-Calahorra, Sofía; Bea, Ana M.; Lamiquiz-Moneo, Itziar; Baila-Rueda, Lucía; Cenarro, Ana; Civeira, Fernando; Mateo-Gallego, Rocío
Summary: Background & aims: It has not been elucidated if an energy-restricted diet with high protein content could induce a benefit in insulin resistance in subjects with type 2 diabetes (T2DM); and if an adipose tissue functionality improvement could mediate this effect. We aimed to assess the effect of energy-restricted diets with standard (18% from total calories; SP) vs high (35%) protein (HP), mainly coming from lean animal source, composition on glucose metabolism and adipokine concentration in overweight and obese subjects with T2DM. HOMA-IR change was the primary outcome. Methods: Six-month weight-loss intervention including 73 subjects (43.8% men, 55.6 ± 8.37 aged and 32.8 ± 3.67 of BMI) with T2DM that were randomized to follow one of two calorie-restricted diets with the following distribution of calories: 18% (0.75 [95%CI: 0.71–0.78] g/kg/day) protein, 52% carbohydrates and 30% fat, or 35% (1.34 [95%CI: 1.27–1.41] g/kg/day) protein, 35% carbohydrates, and 30% fat. Anthropometric, clinical, biochemical (involving leptin, RBP4 and adiponectin) and lifestyle assessments were performed. Results: Sixty-seven participants completed the study. Weight loss homogenously decreased among diets. HOMA-IR in HP diminished 2-fold than in SP diet ( P = 0.023 and P = 0.004 at 3 and 6-months between diets). Participants following HP diet showed higher decrease in insulin, in glucose at 6-months ( P = 0.004) and in HbA1c at 3-months ( P = 0.003). RBP4 and leptin significantly decreased in both diets although no differences were found between diets. Adiponectin increased by 6.05% and 29.9% at 3-months in SP and HP diets, respectively ( P = 0.167), and 23.7% and 53.5% at 6-months in SP and HP diets ( P = 0.219). Adiponectin variation was inversely correlated with HbA1c, insulin and HOMA-IR changes at 6-months. Conclusions: An energy-restricted diet containing 35% of total calories coming from protein lead to a greater improvement in glucose homeostasis, indicated by HOMA-IR and fasting plasma insulin concentrations, irrespective of weight loss in subjects with prediabetes or early stages of T2DM. This effect cannot be explained by changes in plasma concentration of adipokines. Clinical trial registration: The clinical trial has been registered in ClinicalTrials.gov (Identifier: NCT02559479 ).